Inertial Extragradient Methods for Solving Split Equilibrium Problems - Suthep Suantai; Narin Petrot; Manatchanok Khonchaliew (Mathematics, 2021)
This paper presents two inertial extragradient algorithms for finding a solution of split pseudomonotone equilibrium problems in the setting of real Hilbert spaces. The weak and strong convergence theorems of the introduced algorithms are presented under some constraint qualifications of the scalar sequences. The discussions on the numerical experiments are also provided to demonstrate the effectiveness of the proposed algorithms.